2012
DOI: 10.1673/031.012.14201
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of Immatures of the South American Plant Hopper,Taosa(C.)longula

Abstract: Descriptions of the immature stages of Taosa (Cuernavaca) longula Remes Lenicov (Hemiptera: Fulgoroidea: Dictyopharidae) and a key for their identification is provided for specimens collected on the water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach (Commelinales: Pontederiaceae), in northeastern Argentina and Peru. Newly emerged nymphs from eggs collected in the field were reared in rearing chambers, and each stage was fixed to microscopic examination and illustration. Fifth nymphal instars can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Data on the biological properties and peculiarities of particular organisms, especially those with economic or environmental impact, are of primary interest for a full understanding of their role and interaction with the environment. In general, the biology of dictyopharids is poorly known and data regarding life history are only available for a few species from the Palaearctic (Melichar, 1912; Holzinger & Hausl-Hofstätter, 1994; Nickel & Remane, 2002; Holzinger et al ., 2003; Nickel, 2003; Lessio & Alma, 2008; D'Urso & Mifsud, 2012; Burrows, 2014), Nearctic (Wilson & McPherson, 1981; Wilson & Wheeler, 1992, 2005; McPherson & Wilson, 1995; Liang & Wilson, 2002) and Neotropical (Hernández et al ., 2011; Remes Lenicov et al ., 2012) regions.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the biological properties and peculiarities of particular organisms, especially those with economic or environmental impact, are of primary interest for a full understanding of their role and interaction with the environment. In general, the biology of dictyopharids is poorly known and data regarding life history are only available for a few species from the Palaearctic (Melichar, 1912; Holzinger & Hausl-Hofstätter, 1994; Nickel & Remane, 2002; Holzinger et al ., 2003; Nickel, 2003; Lessio & Alma, 2008; D'Urso & Mifsud, 2012; Burrows, 2014), Nearctic (Wilson & McPherson, 1981; Wilson & Wheeler, 1992, 2005; McPherson & Wilson, 1995; Liang & Wilson, 2002) and Neotropical (Hernández et al ., 2011; Remes Lenicov et al ., 2012) regions.…”
Section: Discussionmentioning
confidence: 99%
“…Cuernavaca longula: Argentina Northeast (Formosa y Chaco) (Remes Lenicov & Hernández, 2010;Hernández et al, 2011b;Remes Lenicov et al, 2012) Brazil West-Central (Mato Grosso do Sul and Perú (Remes Lenicov & Hernández, 2010;Remes Lenicov et al, 2012).…”
Section: Distributionmentioning
confidence: 99%
“…(Pellegrini et al, 2018)]. Our taxonomic assessment of Cuernavaca associated with water hyacinths revealed that C. longula coexist with other related species from the upper Amazon River (Remes Lenicov & Hernández, 2010;Remes Lenicov et al, 2012). These species are sympatric in part of their distribution, and should be properly distinguished among themselves so their potential as biocontrol agents can be more thoroughly explored.…”
Section: Introductionmentioning
confidence: 97%